Pathogenicity and virulence of monkeypox at the human-animal-ecology interface. Issue 1 (31st December 2023) - Islam, Md. Mazharul; Dutta, Pronesh; Rashid, Rijwana; Jaffery, Syed Shariq; Islam, Ariful; Farag, Elmoubashar; Zughaier, Susu M; Bansal, Devendra; Hassan, Mohammad Mahmudul
ABSTRACT: Monkeypox (Mpox) was mostly limited to Central and Western Africa, but recently it has been reported globally. The current review presents an update on the virus, including ecology and evolution, possible drivers of transmission, clinical features and management, knowledge gaps, and research priorities to reduce the disease transmission. The origin, reservoir(s) and the sylvatic cycle of the virus in the natural ecosystem are yet to be confirmed. Humans acquire the infection through contact with infected animals, humans, and natural hosts. The major drivers of disease transmission include trapping, hunting, bushmeat consumption, animal trade, and travel to endemic countries. However, in the 2022 epidemic, the majority of the infected humans in non-endemic countries had a history of direct contact with clinical or asymptomatic persons through sexual activity. The prevention and control strategies should include deterring misinformation and stigma, promoting appropriate social and behavioural changes, including healthy life practices, instituting contact tracing and management, and using the smallpox vaccine for high-risk people. Additionally, longer-term preparedness should be emphasized using the One Health approach, such as systems strengthening, surveillance and detection of the virus across regions, early case detection, and integrating measures to mitigate the socio-economic effects of outbreaks.